Experimental investigation of the frictional behavior of single glass fiber filament - Yang Liu (Journal of Engineered Fibers and Fabrics, 2023)
Fiber friction behaviors are crucial for understanding the ubiquitous frictional damage phenomena in the manufacturing and service processes of multiscale textile reinforcements. This paper investigates the influence of relative velocity and applied load on the frictional behavior between a solitary glass fiber filament and a metal roller. The results of piecewise regression analysis indicate that the apparent coefficient of friction initially decreases with relative velocity, followed by an increase, and subsequently decreases again until stabilizing at higher velocity. Specifically, the maximum values of the coefficient of static friction are observed within the relative velocity range of 1.26–1.68 mm/s, while that of dynamic friction occurs within the range of 0.84–3.94 mm/s; the coefficient of friction reaches stable values within the relative velocity range of 7.87–15.71 mm/s. Under four different tension conditions, the stable values for the coefficient of static friction are 0.336, 0.308, 0.321, and 0.281, while the coefficient of dynamic friction are 0.291, 0.269, 0.273, and 0.232 respectively. Furthermore, the relationship between the coefficient of friction and the applied load reveals that the coefficient of friction decreases as the load increases. Finally, quantitative investigation reveals a strong coupling characteristic between the velocity dependency and load dependency of the apparent coefficient of friction.